Expanding the Coverage Area of a Formation of Robots Through a Mesh Network and a Real Time Database Middleware - Caetano, Leandro J.; Nascimento, Tiago P.; Oliveira, Márcio Adamec L.; Rocha, Gláucio B. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
The communication between robots is essential and of great interest in the robotics research field. It is from it that robots can discover and pass on information about obstacles in their way, pass on to the other robots information about a target that other robot can not detect, determine together which is the best route to follow, among others, until the goals are achieved. The major difficulty in the context where robot communication exists in an ad hoc network is distancing the robots from each other. So that one of them for example, may migrate to another area leaving their initial formation, completing a specific task and return to the starting point, in addition to distancing the whole formation of robots from a central computer. By distancing a robot from the limits imposed by other means will entail a loss of signal compromising communication between them. The challenge, therefore, is to maintain communication between these same elements even though they are apart. The purpose of this article is to demonstrate the feasibility of expanding the coverage area of a formation of robots that use a Real Time Database (RTDB) under an ad hoc network communication, by including them in a Mesh network. According to the performed experiments, we proved that the inclusion of robots in this type of network, and using the RTDB, has added the ability aforementioned thus allowing robot control from a central point, called the Basestation, and therefore enabling the distancing between its components without loss of communication between them.